Development of tungsten diselenide/polyaniline composite nanofibers as an efficient electrocatalytic counter electrode material for dye-sensitized solar cell. (October 2020) - Elindjeane Sheela, Sowbakkiyavathi; Murugadoss, Vignesh; Sittaramane, Ramadasse; Angaiah, Subramania
Graphical abstract: Highlights: WSe2 /PANI composite nanofibers were synthesized to use as CE for DSSC. This CE has high electrocatalytic activity than their individual counterpart. It exhibits high PCE of 8.22% than Std. Pt CE based DSSC. Abstract: In this work, polyaniline nanofibers (PANI NFs) were prepared by a chemical oxidative polymerization method and the tungsten diselenide nanoparticles (WSe2 NPs) were prepared by a simple hydrothermal method. By making use of both these materials, WSe2 /PANI (1:1, 1:2 and 2:1 wt%) composite nanofibers were prepared by mixing them at various ratios with the help of ultrasonication method to use as an efficient counter electrode (CE) for dye-sensitized solar cell (DSSC). The physio-chemical behaviour of pristine PANI, WSe2, std. Pt and WSe2 /PANI composite nanofibers were investigated through X-ray diffractometer (XRD), Raman spectroscopy, field emission scanning microscope (FESEM) and energy-dispersive X-ray spectroscopy (EDAX) studies. The electrocatalytic activity of PANI, WSe2, Std. Pt and WSe2 /PANI CEs were studied by using cyclic voltammetry (CV), electrochemical impedance and Tafel polarization studies. From the electrochemical studies, we observed that WSe2 /PANI (1:1 wt%) CE has good electrocatalytic behaviour towards the reduction of iodide/triiodide (I - /I3 - ) than WSe2 /PANI (1:2 and 2:1 wt%), pristine PANI, WSe2, and Std. Pt. Finally, WSe2 /PANI (1:1 wt%), pristine PANI, WSe2, and std. Pt CEs based DSSC were fabricated and tested. The WSe2 /PANI (1:1 wt%) exhibits an outstanding photoconversion efficiency (PCE) of 8.22%. It revealed that WSe2 /PANI (1:1 wt%) CE has excellent electrocatalytic activity than the pristine PANI, WSe2, and std. Pt and could be used as an alternative to Pt CE for DSSC.